2011
DOI: 10.1007/s00404-011-2151-z
|View full text |Cite
|
Sign up to set email alerts
|

The symptomatology of climacteric syndrome: whether associated with the physical factors or psychological disorder in perimenopausal/postmenopausal patients with anxiety–depression disorder

Abstract: PurposeTo explore whether the symptoms of climacteric syndrome associated with its physical factors or psychological disorder in perimenopausal/postmenopausal patients with anxiety–depression disorder.MethodsWe recruited 78 climacteric patients with anxiety–depression disorder and 72 control participants in perimenopausal/postmenopausal without anxiety–depression disorder for this study. We measured symptoms using the Greene Climacteric Symptom Scale in all cases. We also collected demographic data and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
2
17
0
1
Order By: Relevance
“…Shogaeean et al (3) also observed no significant relationship between depression score and decreased libido. In addition, Zhou et al (34) found similar results, suggesting no significant relationship between depression and the variables of age of women, duration of menopause and BMI. Whereas Bosworth et al (35) reported no difference in the proportion of depressed to non-depressed women in terms of age, Dolatian et al (2) concluded that age is directly proportional to depression in all phases of pre-, peri-and postmenopause.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Shogaeean et al (3) also observed no significant relationship between depression score and decreased libido. In addition, Zhou et al (34) found similar results, suggesting no significant relationship between depression and the variables of age of women, duration of menopause and BMI. Whereas Bosworth et al (35) reported no difference in the proportion of depressed to non-depressed women in terms of age, Dolatian et al (2) concluded that age is directly proportional to depression in all phases of pre-, peri-and postmenopause.…”
Section: Discussionsupporting
confidence: 63%
“…Kakkar et al (38) also found similar results, which is consistent with the results of this study. However, the conflicting results in the study by Zhou et al (34) state that women with higher levels of education are more likely to experience depression during menopause.…”
Section: Discussionmentioning
confidence: 44%
“…Zhou et al [16] found that lower E 2 was correlated with anxiety, depression and somatic symptoms, which may be associated with the onset of anxiety-depression disorder. A long duration of mental stress can cause and aggravate women's endocrine disorders, and affect normal physiological function.…”
Section: Commentsmentioning
confidence: 98%
“…Познание закономерностей КД позволяет обосновать роль медико-социального фактора (гиперболизированное внимание к здоровью, медицине, психиатрам, неадекватно утрированная установка на здоровый образ жизни) в виде психосоматизации как психопатологической реакции на климакс [24]. Психосоматизация обусловлена стремлением «найти болезнь», несмотря на стабильное состояние в климаксе.…”
Section: роль стрессорно-дезадаптирующих факторов в формировании кдunclassified